Strategi Pengembangan Usaha Melalui Perancangan (Digital Marketing) Facebook Pada Martabak Al-Barokah Plaju - Putri Andini; Purwati; Heri Setiawan (Politeknik Negeri Sriwijaya, 2023)
Every MSMEs is encouraged to expand their businesses by the growth of digital technology, which is currently beginning to grow quickly in Indonesia. MSMEs are one of the companies that can benefit from the current environment with numerous communication channels; by leveraging the technology that is already available, MSMEs can develop a digital design that will offer many advantages. In order for Martabak Al-Barokah Plaju MSMEs to be more competitive in this contemporary, entirely digital era, they must constantly stay up to date on new developments. This design aims to increase the number of enthusiasts in Martabak Al-Barokah Plaju MSMEs who currently do not have the ability to compete in digital marketing. Â Â